A Phase 3, Multicenter, Open-Label, 12-Month Extension Safety and Tolerability Trial of Lisdexamfetamine Dimesylate in Adults With Binge Eating Disorder. Issue 3 (June 2017) - Gasior, Maria; Hudson, James; Quintero, Javier; Ferreira-Cornwell, M. Celeste; Radewonuk, Jana; McElroy, Susan L.
Abstract: Background: A 12-month, open-label extension study assessed the long-term safety and tolerability of lisdexamfetamine dimesylate (LDX) in adults with binge eating disorder (BED). Methods: Adults (aged 18–55 y) with BED who completed 1 of 3 antecedent studies were enrolled in a 52-week, open-label extension study (dose optimization, 4 weeks [initial titration dose, 30-mg LDX; target doses, 50- or 70-mg LDX]; dose maintenance, 48 weeks). Safety evaluations included the occurrence of treatment-emergent adverse events (TEAEs), vital sign and weight assessments, and Columbia-Suicide Severity Rating Scale responses. Results: Of the 604 enrolled participants, 599 (521 women and 78 men) comprised the safety analysis set, and 369 completed the study. Mean (SD) LDX exposure was 284.3 (118.84) days; cumulative LDX exposure duration was 12 months or longer in 344 participants (57.4%). A total of 506 participants (84.5%) reported TEAEs (TEAEs leading to treatment discontinuation, 54 [9.0%]; severe TEAEs, 42 [7.0%]; serious TEAEs, 17 [2.8%]). Treatment-emergent adverse events reported in greater than or equal to 10% of participants were dry mouth (27.2%), headache (13.2%), insomnia (12.4%), and upper respiratory tract infection (11.4%). Mean (SD) changes from antecedent study baseline in systolic and diastolic blood pressure, pulse, and weight at week 52/early termination (n = 597) were 2.19 (11.043) and 1.77 (7.848) mm Hg, 6.58 (10.572) beats per minute, and −7.04 (7.534) kg, respectively. On the Columbia-Suicide Severity Rating Scale, there were 2 positive responses for any active suicidal ideations; there were no positive responses for suicidal behavior or completed suicides. Conclusions: In this 12-month, open-label, extension study, the long-term safety and tolerability of LDX in adults with BED were generally consistent with its established profile for attention-deficit/hyperactivity disorder. Abstract : Supplemental digital content is available in the text.